The Effect of Magnitude of Operating Cash Flow and Accrual Earnings on the Level of Earnings Persistence - Triani, Neks; Abbas, Ahmad (Universitas Gorontalo, 2023)
This research aims to disclose the magnitude of operating cash flow and accrual earnings in affecting the level of earnings persistence. The sample of this research was manufacturing firms listed in Indonesia Stock Exchanges. The nexus between variables was tested using random effect model. This research demonstrated that the magnitude value of manufacturing firms is positive on average in the accrual earnings, operating cash flow, and earnings persistence. The result of testing the effect points out that accrual earnings and operating cash flow affect the earnings persistence positively. The level of the earnings persistence has been followed by the magnitude of accrual earnings and operating cash flow indicating that the higher the accrual earnings and operating cash flow, the more persistent the earnings gained by manufacturing firms.